THE EFFECTIVENESS OF READING NARRATIVE TEXT WITH A FLIPBOOK IN STUDYING HISTORY OF PURWOREJO - Masykuri, Edi Sunjayanto (Sosio-Didaktika: Social Science Education Journal, 2025)
This research aims to improve the ability to read narative text in English for the eighth-grade-student in SMP N 2 Adimulyo with Flipbook video media about the History  of Purworejo. The role of reading in the development of science is very important, so there needs to be an effort to improve students' reading comprehension skills. According to  initial observations, it is known that the ability to read narrative text of SMP N 2 Adimulyo students is still low, out of 32 people, only 12 have reached minimum standard of score or 37.5% of all students. This is because teachers do not use interesting media about the history of Purworejo in teaching. Several media can be used to improve students' reading skills, one of which is English Flipbook video media. It is hoped that using Flipbook with audio-visual can make a positive contribution to students. Children's interest in videos provides meaningful emphasis on the need to use Flipbook video media for history and culture subjects in Purworejo. The data collection method uses observation and tests. The data analysis method is descriptive both for qualitative data and for quantitative data. The research was carried out at SMP N 2 Adimulyo with a total of 32 students. The results of the study showed that before being given learning using the English Narrative text Flipbook video media, the average score of students' reading comprehension was 62.70 (57.70%) with a medium category. In cycle 1 after using English Narrative text video media from Flipbook, students' reading comprehension increased to 70 (69.23%) still in the medium category, and in cycle 2 students' reading comprehension ability increased by an average score and a percentage of 81.54 (88.46%) with a very high category.